Construction Details and Observed Earthquake Performance of Unreinforced Clay Brick Masonry Cavity-walls. (May 2016) - Giaretton, Marta; Dizhur, Dmytro; da Porto, Francesca; Ingham, Jason M.
Abstract: Unreinforced masonry (URM) cavity-wall construction is a form of masonry where two leaves of clay brick masonry are separated by a continuous air cavity and are interconnected using some form of tie system. A brief historical introduction is followed by details of a survey undertaken to determine the prevalence of URM cavity-wall buildings in New Zealand. Following the 2010/2011 Canterbury earthquakes it was observed that URM cavity-walls generally suffered irreparable damage due to a lack of effective wall restraint and deficient cavity-tie connections, combined with weak mortar strength. It was found that the original cavity-ties were typically corroded due to moisture ingress, resulting in decreased lateral loadbearing capacity of the cavity-walls. Using photographic data pertaining to Christchurch URM buildings that were obtained during post-earthquake reconnaissance, 252 cavity-walls were identified and utilised to study typical construction details and seismic performance. The majority (72%, 182) of the observed damage to URM cavity-wall construction was a result of out-of-plane type wall failures. Three types of out-of-plane wall failure were recognised: (1) overturning response, (2) one-way bending, and (3) two-way bending. In-plane damage was less widely observed (28%) and commonly included diagonal shear cracking through mortar bed joints or bricks. The collected data was used to develop an overview of the most commonly-encountered construction details and to identify typical deficiencies in earthquake response that can be addressed via the selection and implementation of appropriate mitigation interventions.